CLASSIFICATION BY TYPES OF DEFECT «PRODIR» ON AN INTERNAL SURFACE OF HOT-ROLLED PIPES - N. A. Glazunova; O. V. Rozhkova; I. A. Kovalyova (Литьë и металлургия)
Classification of guide scratches according to the types of defect which allows to define and eliminate in proper time the reasons of the guide scratches formation is offered, consequently the decrease in quantity of inappropriate production by this defect on internal surface of pipes is observed